Ramadan Fasting During the COVID-19 Pandemic; Observance of Health, Nutrition and Exercise Criteria for Improving the Immune System - Moghadam, Majid Taati; Taati, Behzad; Paydar Ardakani, Seyed Mojtaba; Suzuki, Katsuhiko (Frontiers in Nutrition, 2021)
Fasting is one of the religious rituals of Muslims worldwide who refrain from eating foods and liquids every year during Ramadan. This year (2020), Ramadan is very different from previous years due to the outbreak of a terrible microscopic giant called coronavirus disease 2019 (COVID-19). The pandemic COVID-19 has made Ramadan very important this year because the virus has infected millions of people around the world and killed thousands, especially people with immunodeficiency. In dealing with COVID-19, maintaining good hygiene and enhancing the immune system are effective, preventive approaches. Moderate exercise training and proper nutrition are the most important factors to support immune function. Lack of facilities, poor health and many traditions that lead to public community gatherings have made many Islamic countries susceptible to this dangerous virus. In such an unprecedented situation, there are many Muslims who doubt whether they can fast or not. Therefore, the proposal of usable exercise programs and effective nutritional strategies is imperative. In this study, we will look at the health benefits of fasting and its effects on the immune system, together with the important health, nutrition, and exercise advice that fasting people need to follow in the event of a COVID-19 outbreak.